Avaliação da expressão gênica e proteica da via de sinalização WNT/ Beta-catenina em amostra de carcinoma de células escamosas bucal e sua relação com fatores de prognóstico - Andrade, Marília Ferreira (2016)
Oral Squamous Cell Carcinoma (OSCC) is one of the 10 most prevalent lesions and the 20th cause of deaths in Brazil. In most cases the diagnosis is detected in an advanced stage, hence the patient has a poor prognosis. Thus, studies with proteins that are involved in signaling pathways have been widely investigated as possible new therapeutic targets to aid the early diagnosis and prognosis. The Wnt/β-catenin pathway comprises the regulation of a wide variety of physiological processes in different species, with a decisive role in embryonic development, cell proliferation and differentiation. Alterations in components of this pathway have also been reported in neoplasms of the oral cavity and it appears as a natural candidate to be investigated in oral carcinogenesis and tumor progression of the OSCC. Among the various related genes investigated in Wnt/ β-catenin pathway there is the CTNNB1 being β- catenin the most important protein. The aim fo this study was to identify the GSK3β, APC, CCTBN, c-MYC, CCND1 e CDH1 gene expression and its relation to their respective proteins (GSK3β, pGSK3β-Ser9, APC, β-catenin, c-myc, cyclin D1 e E-caderin) in a convenience cohort of OSCC. Associations between clinical and pathological aspects considered possible progression and metastasis markers were verified. All OSCC diagnoses were histologically confirmed and categorized in two groups: non-metastasizing (PNM) and metastasizing primary tumors (PM). For gene expression, it was used the real time PCR approach. For immunohistochemistry proposal, it was performed a TMA technique and all proteins was revealed by the streptavidin-biotin peroxidase method. Most patients were male, avarage age of 60, smokers and drinkers, diagnosed in advanced stage of disease, with lesions measuring less than 4cm and the tongue being the most affected location. The relative expression of all investigated genes was higher in the control group, with p<0,05 for CCND1 and CDH1. The CTNNB1 relative expression decreased in the comparison among the control, PNM and PM groups, being statistically significant between control and PM groups. The immunohistochemical results showed increased expression in OSCC in relation to control, being statistically significant for APC, c-Myc and E-caderin in the PM group. There were not found any associations between expression of GSK3β, pGSK3β-Ser9, APC, β-catenin, c-myc, cyclin D1 e E-caderin and clinical and pathological aspects considered possible progression and metastasis markers. The correlation analysis showed significant positive correlation between c-Myc and β-catenin (p<0,0001). In conclusion, these results indicate that the Wnt/β-catenin pathway seems to be inactivated or not been expressed in OSCC and tumor progression.